Comprehensive Forecast of Demand for Inter-regional Rail Freight Transport - Shirov, Alexander A.; Sapova, Natalia N.; Uzyakova, Elena S.; Uzyakov, Rafael M. (Economy of Regions, 2021)
A forecasting system for calculating the demand for inter-regional rail freight transport is necessary for assessing the growth and development opportunities of transport infrastructure, connectivity of regions and spatial development. We examine the regional economy and interregional relations based on the existing system of rail freight transport. The statistics of the Federal State Statistics Service (Rosstat), international statistical agencies and the data of JSC Russian Railways served as raw data. The research methodology includes input-output methods and models, in particular, a static input-output model, as well as methods of correlation and regression analysis. We calculated projected rail freight traffic for two macroeconomic development scenarios. A better alternative (target scenario) of economic development, demonstrating an average annual economic growth rate of 102.2 % for the period 2015-2035, would lead to a 16.2 % increase in the rail freight traffic by 2035 compared to the baseline scenario. The second scenario is based on the hypothesis of economic stagnation at the level of 1 %. Such an increase is achieved by domestic transport, in which the share of construction freight for approximately 30.9 % of total traffic by 2035, and export transport, where the share of energy freight is 44.1 % of the total. An increase in shipment in total rail freight transport will be provided by enterprises of the Central, Northwestern, Volga and Siberian Federal Districts. The proposed tools allow substantiating the strategic development of the railway system, assessing the cooperation between the economy and rail transport. The results can be used for analytical and predictive support of the strategic development of the railway system in the Russian Federation. The future research will focus on expanding the set of factors for considering the regional characteristics of economic development, a more meaningful assessment of the connectivity of regions, not only in the system of rail freight transport.